The Influence of Job Placement and Job Stress on Teacher Performance - Frilly Angelina Kusuma Putri (Almana : Jurnal Manajemen dan Bisnis, 2020)
Improving employee performance is very important because it is a key factor in a company's success. Job placement and job stress are some of the factors that affect employee performance. This research aims to determine the influence of Job placement and job stress on the performance of study teachers at SDN 208 Luginasari Sukagalih. Job placements can nurture skilled human resources and amdal to accomplish a given task. This analysis uses an independent variable i.e. job placement and working stress, the dependencies of which are the teacher's performance. The population used in this study to collect data was nailed by using a questionnaire that was disseminated by ± 33 people. Statistical methods use path analysis with a partial statistical test (T) and simultaneous test hypothesis testing (test F). The results showed that Job placement and job work significantly impact the performance of teachers at SDN 208 Luginasari Sukagalih.